Corrosion susceptibility of different planes of AlMgScZr alloy produced by selective laser melting. (December 2022) - Chen, Y.X.; Lin, D.Y.; Han, J.C.; Xia, X.J.; Chen, Y.Y.; Hao, W.K.; Yang, B.K.; Hu, P.H.; Chen, S.F.; Lu, Y.J.
Abstract: In this study, the corrosion susceptibility of the Top and Side plane of the AlMgScZr alloy manufactured by selective laser melting (SLM) was investigated by electrochemical tests. The microstructures indicated that an alternately fine and coarse grain could be found in the Top plane and Side plane. The Top plane was mostly dominated by fine grains, while the microstructure in the Side plane primarily consisted of columnar grains. The XRD and TEM results suggested a great deal of nano-size Al3 (Sc, Zr) precipitations were formed in the Top and Side plane. Moreover, the results from the EBSD demonstrated that the texture of the Top plane was closed to {001}〈100〉 but very weak, while the Side plane orientated slightly {011}〈122〉 texture. The electrochemical tests showed that the Top plane exhibited a better corrosion resistance compared with the Side plane. The lower corrosion susceptibility of the Top was mainly attributed to the better grain distribution and weaker texture relative to the Side plane.